2015
DOI: 10.1074/jbc.m115.652263
|View full text |Cite
|
Sign up to set email alerts
|

The Familial British Dementia Mutation Promotes Formation of Neurotoxic Cystine Cross-linked Amyloid Bri (ABri) Oligomers

Abstract: Background: Familial British dementia is a disorder similar to Alzheimer disease and is believed to be caused by the ABri peptide. Results: Cystine-linked oligomers of ABri are toxic to neurons and block long-term potentiation. Conclusion:The type and toxicity of ABri assemblies depends on cystine bond formation. Significance: ABri offers a tractable system to study the structure of disease-causing oligomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…inhibits hippocampal LTP (Cantlon, et al, 2015a), similar to Aβ. The proposal that reduction in Bri2 levels causes FBD and FDD is based on the finding that Bri2 can affect AβPP processing.…”
Section: Bri2 In Familial British and Danish Dementia And Links To Aβppmentioning
confidence: 86%
“…inhibits hippocampal LTP (Cantlon, et al, 2015a), similar to Aβ. The proposal that reduction in Bri2 levels causes FBD and FDD is based on the finding that Bri2 can affect AβPP processing.…”
Section: Bri2 In Familial British and Danish Dementia And Links To Aβppmentioning
confidence: 86%
“…Based on the general consensus that aggregation of Aβ is required for toxicity, we employed a partially aggregated preparation of Aβ(1–42) that contained both amyloid fibrils and Aβ monomer [ 4 , 62 ]. This preparation is referred to as 1/2 t max , because it is produced by incubating Aβ monomer for a period that yields half of the maximal level of thioflavin T. When used at concentration ≥ 10 μM, 1/2 t max can cause the compromise and death of cultured rodent and human neurons within a period of a few days [ 4 , 62 ]. Synthetic monomer Aβ (1–42) (human sequence) was obtained from rPeptide (A-1165-2).…”
Section: Methodsmentioning
confidence: 99%
“…One hypothesis focuses on a toxic gain of function, in which mutations give rise to ABri or ADan that form toxic aggregates ( Figure 2A ). In vitro , aggregation studies have shown that ABri and ADan form oligomers, protofibrils and fibrils [ 51 , 53 ], while under similar conditions Bri does not readily aggregate and the assemblies Bri does form are not toxic [ 56 ]. Further, Tg-FDD and ADanPP7 mice exhibit age-dependent amyloid deposition associated with neuritic dystrophy, microglial activation, aberrant tau phosphorylation and deficits in motor control [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed we propose that etiology of FBD is best explained by both a toxic gain and loss of function. At a molecular level FBD is directly attributable to the increased ability of the cysteines within the ABri domain of FBD-BRI2 to form intermolecular cross-links that act: (i) to destabilize FBD-BRI2 and make it less prone to proteolytic maturation, and (ii) to give rise to the formation of covalently stabilized toxic ABri oligomers ( Figure 3 ) [ 56 ]. In this model reduced levels of mature BRI2 contribute to impaired synaptic plasticity, and cystine-linked ABri oligomers cause aberrant changes in tau and consequent neuronal loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation